2015
DOI: 10.1158/1078-0432.ccr-14-2112
|View full text |Cite
|
Sign up to set email alerts
|

SLFN11 Is a Transcriptional Target of EWS-FLI1 and a Determinant of Drug Response in Ewing Sarcoma

Abstract: Purpose SLFN11 was identified as a critical determinant of response to DNA targeted therapies by analyzing gene expression and drug sensitivity of NCI-60 and CCLE datasets. However, how SLFN11 is regulated in cancer cells remained unknown. Ewing’s sarcoma (ES), which is characterized by the chimeric transcription factor EWS-FLI1, has notably high SLFN11 expression, leading us to investigate whether EWS-FLI1 drives SLFN11 expression and the role of SLFN11 in the drug response of ES cells. Experimental Design … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
85
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 47 publications
2
85
0
Order By: Relevance
“…Additionally, we tested two Ewing's sarcoma cell lines, EW8 and A673 with high SLFN11 transcripts [25, 26]. SLFN11 protein levels were consistent with transcript levels (Figure 1B).…”
Section: Resultsmentioning
confidence: 71%
“…Additionally, we tested two Ewing's sarcoma cell lines, EW8 and A673 with high SLFN11 transcripts [25, 26]. SLFN11 protein levels were consistent with transcript levels (Figure 1B).…”
Section: Resultsmentioning
confidence: 71%
“…To identify recurrently differentially expressed genes, we generated a meta p value for each gene based on the degree of differential expression in each of the individual models (Figure 3B). Schlafen family member 11 ( SLFN11 ), a gene that we and others have reported as being critical to sensitivity to DNA damaging agents (Barretina et al, 2012; Lok et al, 2016; Sousa et al, 2015; Stewart et al, 2014; Tang et al, 2015; Zoppoli et al, 2012), was among the most significantly downregulated genes. Cancer-testis antigens, a family of genes that are highly sensitive to epigenetic perturbation (De Smet et al, 1999), were significantly upregulated, as well as Twist family bHLH transcription factor 1 ( TWIST1 ), a gene previously described to play an important role in acquired resistance to a variety of agents (Fischer et al, 2015; Zheng et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…We then interrogated the role of SLFN11 in the context of acquired chemoresistance, as it had been previously implicated as a factor regulating DNA damage repair (Mu et al, 2016) and was shown to correlate with responses to DNA damaging agents in vitro (Barretina et al, 2012; Sousa et al, 2015) and in vivo (Tang et al, 2015). SLFN11 is bi-modally expressed when examined across cancer cell lines within the Cancer Cell Line Encyclopedia (CCLE), as well as within SCLC in both primary tumor (Lok et al, 2016) and cell lines (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…No such predictive biomarker has been defined for SCLC. Previous in vitro analyses in colon cancer and Ewing sarcoma cell lines have implicated SLFN11 as a correlate of response to conventional DNA damaging agents, including topoisomerase poisons and cisplatin (25, 44, 45). In this study, we substantially expand our knowledge of SLFN11 by showing for the first time that SLFN11 is a strong predictor of SCLC sensitivity to PARP inhibitors, and confirm these findings in vivo through multiple PDX models.…”
Section: Discussionmentioning
confidence: 99%